Facebook Engagement Among Philippine Junior High Students: Stimulating Connectedness In The New Normal - Grengia, Frederick (ETERNAL (English, Teaching, Learning and Research Journal), 2024)
ABSTRACT Given the prevalence of social media among young millennial learners, this study was conducted to see how teacher-student connectivity via Facebook influences student engagement in junior high school.Student engagement , which is critical to a student's academic achievement, is influenced by a variety of factors, including the typical teacher-student relationship.The two hundred fifty-three (253) students were surveyed using Student Engagement in Schools Questionnaire (SESQ) that examined the extent of their interest, involvement, and drive to succeed in the class, particularly in the class of their teachers who were their Facebook friends. Twenty-two (22) teachers were polled using a self-report questionnaire. Five of them were chosen at random for an interview on their Facebook interactions with students and their views on such connections. Correlational method was used. The findings imply that when teachers use Facebook to develop a social connection with junior high school students, even if the link is simple and routine, it has a significant impact on the students' affective, behavioral, cognitive, and academic involvement in the classroom.